The economics of desertification, land degradation, and drought: Toward an integrated global assessment - Nkonya, Ephraim M.; Gerber, Nicolas; Baumgartner, Philipp; von Braun, Joachim; De Pinto, Alessandro; Graw, Valerie; Kato, Edward; Kloos, Julia; Walter, Teresa (International Food Policy Research Institute, 2011)
Attention to land degradation and environmental pollution has increased significantly in the past 25 years, largely due to greater levels of international cooperation and recognition that local changes in land resources have global impacts. As the world's focus on climate change increases, so, too, does the attention being paid to drought and its rise in frequency and severity. Despite this heightened global awareness, action to prevent or mitigate land degradation and drought at national or international levels has been limited, primarily because there are limited assessments regarding the cost of land degradation. Past global assessments have largely focused on the biophysical impacts of land degradation while little has been done to assess its global economic costs or the costs-versus-benefits of preventing or mitigating it. Additionally, past studies have largely focused on loss of on-site productivity and have paid limited attention to the off-site costs of land degradation and off-site benefits of land improvement. As part of the effort to address these and other gaps, this study was undertaken to prepare a framework for global assessment of the economics of desertification, land degradation, and drought (E-DLDD).